Lyotard, art, seeing. (1st September 2013) - Mapp, Nigel
This araticle examines elements of Jean-François Lyotard's paradoxical negotiations with aesthetic experiences in order to characterize his critical involvement with discursivized forms of knowing and explanation. These elements are offered as salient and salutary correctives to the symmetrical dogmas of disenchanting naturalisms and culturalisms currently programming typical misprisions of the aesthetic. Lyotard's 1971 Discourse, Figure, as well as some of his later writings on visual art and artists, are not interpretatively integrated here but instead explored in terms of an anti-discursive logic that actually animates what appear to be their own anti-aesthetic commitments and conclusions. The article tracks the ambivalent, but persistent, role that perception, art-medium and sensate experience play in Lyotard's efforts to see beyond them. This result impacts not only on the kinds of 'demystification' his work should be seen to espouse, but on that pervasive pseudo-category itself.